Canadian literary fare - Cooke, Nathalie; Boyd, Shelley, 1974-; Moyer, Alexia (Carleton library series, 2023)
"When literary writers place food in front of their characters--who after all do not need sustenance--they are asking readers to be alert to the meaning and implication of food choices. As readers begin to listen closely to these cues, they become attuned to increasingly layered stories about why it matters what foods are selected, prepared, served, shared, and with whom, where, and when. In Canadian Literary Fare Nathalie Cooke and Shelley Boyd explore food voices in a wide range of Canadian fiction, drama, and poetry, drawing from their formational blog series with Alexia Moyer. Thirteen short vignettes delve into metaphorical taste sensations, telling of how single ingredients such as garlic or ginger, or food items such as butter tarts or bannock, can pack a hefty symbolic punch in literary contexts. A chapter on Canada's public markets finds literary food voices sounding a largely positive note, just as Canadian journalists trumpet Canada's bountiful and diverse foodways. But in chapters on literary representations of bison and Kraft Dinner, Cooke and Boyd bear witness to narratives of hunger, food scarcity, and social inequality with poignancy and insistence. Canadian Literary Fare pays heed to food voices in the works of Tomson Highway, Rabindranath Maharaj, Alice Munro, M. NourbeSe Philip, Eden Robinson, Fred Wah, and more, inviting readers to listen for stories of foodways in the literatures of Canada and beyond."--